Cell-type-specific responses to single-pulse electrical stimulation of the human brain - Rhiannon L. Cowan; Tyler S. Davis; Edward M. Merricks; Bornali Kundu; Ben Shofty; Shervin Rahimpour; Catherine A. Schevon; John D. Rolston; Elliot H. Smith (Brain Stimulation)
Background: Currently approved human brain stimulation therapies, ranging from deep brain stimulation to responsive neuromodulation, use macro electrodes to deliver current to the brain. Despite daily clinical use, it remains fundamentally unknown how human neurons respond to intracranial stimulation. Objective: We address this knowledge gap by characterizing cell-type-specific firing rate (FR) responses to broadly distributed single pulses of electrical stimulation as part of a common clinical procedure for epilepsy patients. Methods: We recorded isolated neurons on microwires implanted into the medial temporal and frontal lobes of 30 epilepsy patients while stimulating macroelectrode contacts. Results: Proportions of units classified as interneurons and principal cells corresponded with those previously reported. To see how stimulation affected neuronal activation, we calculated FR change between pre-stimulation and post-stimulation time windows and observed that from 174 modulated units 91 % showed FR suppression (Cohen's h = 0.77, large effect). We then characterized stimulation-evoked changes in FR to gain insight into cell-type-specific responses. Additionally, we observed that FR responses were modulated by stimulation distance, where local stimulation (within ∼40 mm) could evoke instantaneous firing, while distant stimulation reliably suppressed firing. Finally, we analyzed units within the seizure onset zone, revealing unique waveshapes and FR responses to stimulation. Conclusions: This study bridges a gap in the neuromodulation field by examining the single-unit, cell-type-specific FR responses to direct electrical stimulation of the human brain. We show that low-frequency, single-pulse stimulation broadly elicits suppression, but parameters, such as distance, can have diverse effects on FR. This work informs the neuronal basis of stimulation-evoked potential generation, cell-type-specific responses to stimulation, and has clinical implications for the diagnosis and treatment of drug-resistant epilepsy.